Multi-objective nonlinear sum of fractional optimization problems with non-convex constraints using duality based branch and bound algorithm - Bhati, D.; Singh, P. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The present paper investigates the solution of multiobjective nonlinear sum of fractional optimization problems. A duality based branch and bound cut method is developed to obtain efficient solution and the methodology is validate by proving the theoretical assertions for the solution. The present method is the extension of the work P. P. Shen, Y. P. Duan and Y. G. Pei[19] which developed for single objective sum of ratios nonlinear optimization problem. The proposed method is coded in matlab (version 2014b). Two numerical problems are considered for solving by using the proposed method and global optimal solution is obtained.